STRENGTHENING COMMUNITY POLICING AND THE PLACE OF LEGISLATIVE OVERSIGHT: A STUDY OF THE HARMONISED SURVEILLANCE GUARD - OLANIYAN , Taiwo Abimbola; RAJI , Oluwakemi C. (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
Provision of adequate security is a social obligation for the survival of any society. States ensure that proper measures are taken to protect people’s lives and properties within their geographic spaces. Security’s critical importance explains why states from time to time make efforts to safeguard their neighbourhoods to police themselves from harm. Security involves the act of prevention and protection which ensures that lives and properties are safe. Issues concerning security and safety have been a major challenge in Nigeria. The poor and inadequate security personnel to protect citizens highlighted the need for critical intervention. The Harmonised Surveillance Guard, a renowned local community policing outfit, emerged in response to the increasing wave of armed robberies and insurgency in many parts of the country. Its emergence was also necessitated by the need to complement the shortfall in police officers and to adequately guard and protect citizens. Using historical and analytical approaches and drawing from primary and secondary sources, the article examines the activities of the Harmonised Surveillance Guard in maintaining internal security in Nigeria. The article also examines the way by which the legislature can address the lack of implementation of community policing by the Nigerian Police through strict oversight. Although the Harmonised Surveillance Guard exist to adequately complement the Nigerian Police in the policing of Ede and its environs, the article notes that local communities welcome this outfit’s crime-fighting strategies and are strongly in support of its coordinated security arrangements. The article concludes that the presence of the Harmonised Surveillance Guard has put in check on several cases of criminal activities in communities where they are located which the Nigerian police have hitherto failed to prevent satisfactorily.